2015
DOI: 10.1007/s12665-015-4673-3
|View full text |Cite
|
Sign up to set email alerts
|

Review on groundwater recharge in carbonate aquifers from SW Mediterranean (Betic Cordillera, S Spain)

Abstract: This paper presents a review of groundwater recharge assessment in some 50 carbonate aquifers of the extreme SW Mediterranean domain (Betic Cordillera, southern Spain), an area highly vulnerable to climate change. The selected aquifers represent a broad range of meteorological and geological conditions, and consequently results can be expanded eastward to other Mediterranean aquifers. The methods most commonly applied for recharge assessment over the past 20 years are aquifer water budget and soil water balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
3
20
0
1
Order By: Relevance
“…The physical and climatic characteristics of the province of Alicante determine a low average recharge rate (12%) from total rainfall. This value is typical of semiarid areas and is within the range of values found for some aquifers in this and other regions with similar characteristics [91,[95][96][97][98]. This explains why the entries in many of the provincial systems have been unable to balance the intensive extractions that have taken place for decades, especially in Sectors IV, VI, and VII.…”
Section: Discussionsupporting
confidence: 76%
“…The physical and climatic characteristics of the province of Alicante determine a low average recharge rate (12%) from total rainfall. This value is typical of semiarid areas and is within the range of values found for some aquifers in this and other regions with similar characteristics [91,[95][96][97][98]. This explains why the entries in many of the provincial systems have been unable to balance the intensive extractions that have taken place for decades, especially in Sectors IV, VI, and VII.…”
Section: Discussionsupporting
confidence: 76%
“…This represents 1.56×10 6 m 3 •yr −1 •km −1 suggesting a still low "natural" SGD value. A recharge ratio of between 23 and 52% (average 35%) for karstified carbonates [Allocca et al, 2014, Arfib and Charlier, 2016, Baudement et al, 2017, Martos-Rosillo et al, 2015, Polemio, 2016, Zagana et al, 2007, and between 10 and 21% (average 16%) for detritic aquifer formations [Séraphin et al, 2016, Yagbasan, 2016, Zagana et al, 2007 were reported in the north Mediterranean area (Spain to Turkey). Given that karstic aquifers represent almost 20% of the coastal areas in Mediterranean Europe [Goldscheider et al, 2020], an average value of about 20% for the recharge ratio, therefore tenfold higher than in the southern part of the Mediterranean domain (2 to 3%), can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…karst areas as karst spring discharges are under-represented. Access to data has been identified as a major impediment in quantifying karstification, modelling flow dynamics and transport processes of karst groundwater 2,17 . Studies involving large-scale parameter estimation or comparative studies in karst hydrology are still fairly rare and unrealistic representations of hydrological processes in karst regions can still be found in many large-scale hydrological models 17,18 .…”
mentioning
confidence: 99%